2009
DOI: 10.2174/1874917800902010001
|View full text |Cite
|
Sign up to set email alerts
|

The Pleasure of Being Aggressive in Male Incarcerated Criminals

Abstract: Maximization of pleasure (hedonicity) is a major mechanism in human decision-making by optimizing behavior, as previous research has shown on both sensory pleasure and purely mental pleasure (such as playing videogames or solving mathematical problems). Our group also documented that pleasure is a major factor in decision-making in social situations related to interpersonal aggression: people tend to make aggressive behavioral decisions as a function of the resulting pleasure. The present study tried to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Cabanac and his group [17] suggest that cognitive dissonance may also be a possible mechanism for explaining the results found in our previous studies on the pleasure of aggressive behavior [7,8,14,15,22]. According to these results, the difference between aggressive and nonaggressive people would partially be found in their values, in their acceptance of the social norms, and consequently in the higher or lower need of reducing the tension caused by discordance between pleasure and aggression.…”
Section: Cognitive Dissonancementioning
confidence: 60%
See 3 more Smart Citations
“…Cabanac and his group [17] suggest that cognitive dissonance may also be a possible mechanism for explaining the results found in our previous studies on the pleasure of aggressive behavior [7,8,14,15,22]. According to these results, the difference between aggressive and nonaggressive people would partially be found in their values, in their acceptance of the social norms, and consequently in the higher or lower need of reducing the tension caused by discordance between pleasure and aggression.…”
Section: Cognitive Dissonancementioning
confidence: 60%
“…Applying the same methodology to inmates, it was shown that their election also shared a higher satisfaction or pleasure, even if this specific population was more prone to violence than the general population: they tended to solve conflicts by more aggressive means [14,15]. Such a result is consistent with a fundamental role of hedonia in decisionmaking, showing that the trend to maximize pleasure or minimize displeasure when it comes to make an aggressive decision is indeed a deeply rooted mechanism of decisionmaking that largely transcends cultural biases or pathological borderlines.…”
Section: Aggression and Pleasurementioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies on a 'normal' population (Ramírez et al , 2005 and on inmates serving longterm for severe crimes (Ramírez, Millana, Toldos-Romero, Bonniot-Cabanac, & Cabanac, 2007), both groups rated mildly aggressive behaviours as pleasant and selected them as their preferred responses to mild social conflicts. These similar results were congruent with our previous analysis on justification of aggression in different cultures suggesting a certain universal moral code, common to all humans (Ramírez, 1991(Ramírez, , 1993(Ramírez, , 2007bRamírez, Lagerspetz et al 2001).…”
Section: Introductionmentioning
confidence: 99%